Emulsion‐Induced Polymersomes Taming Tetrodotoxin for Prolonged Duration Local Anesthesia (Adv. Therap. 1/2023). Issue 1 (18th January 2023) - Li, Xiaosi; Li, Qi; Song, Shenghan; Stevens, Amy O.; Broemmel, Zach; He, Yi; Wesselmann, Ursula; Yaksh, Tony; Zhao, Chao
Abstract : In article number 2200199, Chao Zhao and co‐workers report emulsion‐induced polymersomes. Through a simple emulsification process, the polymer forms polymersomes within seconds, and the formed polymersomes effectively encapsulate water‐soluble drugs in them.